2013
DOI: 10.1017/s1041610213000653
|View full text |Cite
|
Sign up to set email alerts
|

Progression of Alzheimer's disease during a three-year follow-up using the CERAD-NB total score: Kuopio ALSOVA study

Abstract: The CERAD total score is a suitable and sensitive follow-up tool in longitudinal AD trials. Cognition progression rates did not significantly differ between study groups; however, patients with very mild AD at baseline had milder neuropsychiatric symptoms after long-term follow-up. This emphasizes the importance of early diagnosis and assessment of neuropsychiatric symptoms at the diagnostic visit and during follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
1
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 27 publications
4
37
1
3
Order By: Relevance
“…Although AD is a progressive disorder, we found that a large proportion of patients experienced no or little decline during two years of follow-up, which is consistent with other studies [5,6,8,9]. The large proportion of slow progressors illustrates the need to look beyond the mean progression rates to understand the considerable variance in disease course in AD.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Although AD is a progressive disorder, we found that a large proportion of patients experienced no or little decline during two years of follow-up, which is consistent with other studies [5,6,8,9]. The large proportion of slow progressors illustrates the need to look beyond the mean progression rates to understand the considerable variance in disease course in AD.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with this finding, two memory clinic studies found that 25-30% of the patients were stable over a period of two to three years [5,8].…”
Section: Introductionsupporting
confidence: 57%
See 2 more Smart Citations
“…A longitudinal decline in instrumental ADLs usually precedes the decline of basic/self-care ADLs. 21,22 Although predictors Figure 1 A) Estimated marginal means for fine motor dexterity (summed time of four trials in 9HPT) and cognitive functioning (DRS total score) after covariating for age (mean, 74.2) and education (mean, 4.6). Significant group differences in fine motor dexterity were found between controls and MDaMC (p = 0.009), controls and AD (p o 0.001), and aMCI and AD (p = 0.004).…”
Section: Discussionmentioning
confidence: 99%